An Integrative Study of Aortic mRNA/miRNA Longitudinal Changes in Long-Term LVAD Support - Dlouha, Dana; Ivak, Peter; Netuka, Ivan; Benesova, Sarka; Tucanova, Zuzana; Hubacek, Jaroslav A (International journal of molecular sciences, 2021)
Studying the long-term impact of continuous-flow left ventricular assist device (CF-LVAD) offers an opportunity for a complex understanding of the pathophysiology of vascular changes in aortic tissue in response to a nonphysiological blood flow pattern. Our study aimed to analyze aortic mRNA/miRNA expression changes in response to long-term LVAD support. Paired aortic samples obtained at the time of LVAD implantation and at the time of heart transplantation were examined for mRNA/miRNA profiling. The number of differentially expressed genes (Pcorr < 0.05) shared between samples before and after LVAD support was 277. The whole miRNome profile revealed 69 differentially expressed miRNAs (Pcorr < 0.05). Gene ontology (GO) analysis identified that LVAD predominantly influenced genes involved in the extracellular matrix and collagen fibril organization. Integrated mRNA/miRNA analysis revealed that potential targets of miRNAs dysregulated in explanted samples are mainly involved in GO biological process terms related to dendritic spine organization, neuron projection organization, and cell junction assembly and organization. We found differentially expressed genes participating in vascular tissue engineering as a consequence of LVAD duration. Changes in aortic miRNA levels demonstrated an effect on molecular processes involved in angiogenesis.
Keywords: Humans; Longitudinal Studies; messenger RNA; Heart Failure; srdeční selhání; transplantace srdce; lidé středního věku; regulace genové exprese; MicroRNAs; Aortic Valve Disease; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Heart Transplantation; Adult; RNA, Messenger; podpůrné srdeční systémy; ženské pohlaví; longitudinální studie; Gene Expression Regulation; Male; Middle Aged; Adolescent; stanovení celkové genové exprese; onemocnění aortální chlopně; Heart-Assist Devices; Young Adult; mikro RNA; Gene Expression Profiling; mužské pohlaví; mladiství